Gwen Meredith interviewed by Hazel de Berg in the Hazel de Berg collection - Meredith, Gwen, 1907-2006.; De Berg, Hazel, 1913-1984. (1975)
Meredith speaks of her debut in radio writing ; her radio serials 'The Lawsons' and 'Blue Hills'.
Also available online
Transcript available (16 leaves)
Keywords: Meredith, Gwen, -- 1907-2006 -- Interviews; Meredith, Gwen, -- 1907-2006; Radio authorship; Women dramatists, Australian -- Interviews